Vilaprisan for the treatment of symptomatic endometriosis: results from a terminated phase 2b randomized controlled trial - Taylor, Hugh S. (Elsevier Inc., 2025)
Objective: To evaluate the efficacy and safety of 2 doses of vilaprisan vs. placebo in participants with symptomatic endometriosis.
Design: Multicenter, randomized, double-blind, placebo-controlled, parallel-group phase 2b trial (NCT03573336). The initially planned sample size was 315 patients. Recruitment was paused to assess long-term toxicity findings in rodents; although the findings were assessed as likely to be of limited clinical relevance in humans, the study was closed by the sponsor. During the pause, enrolled patients completed 3 or 6 months of treatment per their assigned regimen.
Setting: University hospitals, a regional hospital, and a private clinic.
Patients: Premenopausal adults with confirmed endometriosis and moderate-to-severe pelvic pain (≥4/10 on a numerical rating scale) were enrolled. Inclusion required protocol adherence, including ≥24 diary entries, and an average pain score of ≥3.5.
Intervention: Participants were randomly assigned 1:1:1 to receive vilaprisan (2 mg), vilaprisan (4 mg), or placebo.
Main outcome measures: The primary outcome was a change in the 7-day mean "worst pain" (per the endometriosis symptom diary item 1) from baseline to month 3. All analyses were descriptive only.
Results: Eight participants were randomly assigned to treatment before the study pause: 6 received vilaprisan (4 mg, n = 4 and 2 mg, n = 2), and 2 received placebo. The 6 vilaprisan recipients experienced an improvement in endometriosis-associated pelvic pain, whereas the 2 placebo recipients experienced no change or increased pain; all 8 participants had decreased use of pain medication. Bleeding intensity decreased from baseline in the vilaprisan group.
Conclusion: The study findings suggest that vilaprisan may improve outcomes in patients with endometriosis. Further studies in larger populations would be needed to accurately assess treatment effects.